AMBON DI BAWAH ORDE BARU: TRANSFORMASI KAPITALISME PADA MASYARAKAT PINGGIRAN - Hatib Kadir (IAIN Ambon, 2019)
ABSTRACT: Using the approach of Karl Polanyi (2014), this paper studies three great transformation take place in Ambon Island during the 1970s t0 1990s. Those transformation are on land, money and transportation. Money transforms local people to acquaint with the price system. On the other hand, the needs of consumption increase when money is introduced. Using money, local Moluccans can send their children to the higher school as well as allocate to buy more machinery works. The machinization also accelerates rural people to work faster and more efficient. The questions from this paper is who are the people who bring all of these social and economic transformations? The author found that the coming of voluntary migrants from Sulawesi, Java, and Padangese any other Island in Indonesia play significant role to change the Moluccan system economic and social systems. These migrants dominate exchanges from the production level in the orchards to the rural and urban marketplaces. They play both as traders and middlemen. The Butonese, migrants from Sulawesi, are the most significant suppliers and middlemen that bring rural commodities to sell to the Chinese Moluccan in the city. Chinese Moluccan mostly are shop owners who do not have a direct in touch with the local Moluccan landowners in the rural areas. They also play a role as moneylender for Butonese to buy cloves and nutmeg from the rural areas. Therefore, it is Butonese that have direct contact with the rural Moluccans. Despite the authoritarian regime of the New Order, in the economic field, the State tend to let people to constitute their own business, before finally in the mid of 1990s, The Clove Support and Trading Board (BPPC) under the authority of Tommy Suharto, the son of Indonesian President, took over the business by monopolize the clove trade system. Keywords: Economic Transformation, ethnic economy, exchanges, middlemen, monetization.